The New Concept of Aswaja An-Nahdliyah Values: An Investigation of Religious Moderation and Citizenship Teaching in Pesantren-Integrated Schools - Ikhsan, M. Alifudin; Marzuki, Marzuki; Suharno, Suharno; Anam, Faris Khoirul; Muzdalifah, Zahrotul; Arawindha, Ucca (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2024)
This study aims to understand the implementation of the new concept of Aswaja an-Nahdliyah in teaching religious moderation and citizenship in pesantren integrated schools. It is based on the urgency of strengthening the role of pesantren in shaping a moderate understanding of religion and citizenship amid global challenges in the form of increasing radicalism and extremism. The research method used was a qualitative approach with a multi-site case study design. The research was conducted in three pesantren integrated schools in Malang Regency, East Java, which represent the types of salaf, modern, and semi-modern pesantren. Data were collected through deep interviews, participant observation, and document analysis. The results showed that the development of a new concept of Aswaja an-Nahdliyah was carried out through the systematic integration of values into the curriculum, the adoption of interactive teaching methods, and the development of teaching materials that integrate traditional values with contemporary issues. The teaching of Aswaja an-Nahdliyah values contributes significantly to the formation of religious moderation attitudes among santri, reflected in an increased understanding of key concepts of Islamic moderation and the ability to apply Aswaja an-Nahdliyah principles in responding to contemporary issues. This research provides valuable insights for the development of educational policies that promote religious moderation and strengthen civic values in Indonesia. It also makes an important contribution to the formulation of educational strategies that are adaptive to the demands of the times, while still maintaining the essence of fundamental Aswaja values